Optimization of complete denture treatment for flat ridges with various occlusal schemes in distributing stress and masticatory force - Lubis, Dina HN.; Ismet D. Nasution; Putri WU. Ritonga (Indonesian Journal of Prosthodontic, 2025)
Edentulism impacts an individual's ability to chew and digest food effectively, leading to a decline in quality of life. This issue worsens with flat ridge conditions, which increase mucosal stress distribution under masticatory load. Excessive stress beyond the pressure-pain threshold results in poor masticatory performance, emphasizing the importance of selecting an ideal occlusal scheme for such ridge conditions. The basic concept of occlusal schemes aims to preserve residual ridge integrity and prevent further damage over time. Lingualized and monoplane occlusions are schemes that can be used in flat ridge complete dentures to evenly distribute stress and reduce masticatory load. The stress distribution between dentures and the underlying dental mucosa is critical for understanding the relationship with the patient's pressure-pain threshold. Therefore, in vitro measurements can simulate stress distribution and masticatory force assessments. This literature review discusses the measurement of stress distribution and masticatory force on flat ridge complete dentures with different occlusal schemes. Keywords: complete denture; flat ridge; stress distribution; masticatory force; direct measurement